Partisipasi Pemuda Dalam Membangun Data Desa Presisi di Kelurahan Situ Gede, Kota Bogor - Badar Muhammad; Sofyan Sjaf; Zessy Ardinal Barlan; Grace Natalie (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Until now, the polemic experienced in the process of village development is the development of accurate data-based. The three important elements needed to produce village data sources that describe the actual condition of villages in Indonesia are efficient, effective, and precise. The presence of Precision Village Data is a community service effort, so that the villagers can build, verify, and have accurate data on the actual condition of the village as the foundation of village development. In its implementation, Data Desa Presisi in Situ Gede Village involved a total of 35 representatives of 10 RW who existed as a team of enumerators with the help of 1 lecturer serving, 2 alumni serving, and 8 IGTF students to work with the community to build Precision Village Data. Based on the implementation of The Precision Village Data of Situ Gede Village, the community of Situ Gede Village has the potential to be the target of a service program in the form of science and technology transfer. Through the presentation of Data Desa Presisi Situ Gede Village, it can be described that not only human resources, the potential of SDA owned Situ Gede Village is interesting to be studied, especially in the field of family-based yard land utilization. IPB campus as a state university whose existence is surrounded by villages / villages, it is necessary to identify the forms of development programs and appropriate community service with data-based Precision Village. Innovations produced by academics are not only to be created and disseminated, but must be able to provide tangible benefits to society. Keywords: development, youth, precision